SANS STUDIES ON THE BOVINE SERUM ALBUMIN DENATURATION IN THE PRESENCE OF SDS - Dwi Rahayu; Arum Patriati; Nadi Suparno; Edy Giri Rachman Putra (Jurnal Sains Materi Indonesia, 2020)
The effect of the presence of sodium dodecyl sulfate (SDS) on the denaturation of bovine serum albumin (BSA) has been studied using 36 m small-angle neutron scattering (SANS) BATAN spectrometer (SMARTer). The neutron scattering data reduction used the Graphical Reduction and Analysis SANS Program (GRASP) software, and the fitting process used the IGOR SANS Analysis software. The denaturation process was identified by observing the changes BSA globular structure. The experimental results showed the addition of SDS at low concentrations (2 mM, 5 mM, 10 mM) into BSA solution at pH 7 do not cause a significant change in the size of the BSA globular structure. The SANS scattering profile of BSA fitted with the triaxial ellipsoid model, a simple shape approach for protein globular structure. The fitting result showed the semi-axis B for BSA in the addition of 2 mM, 5 mM, 10 mM SDS were 33.8 Å, 33.8 Å, and 37.8 Å, respectively. While the semi-axis A and semi-axis C were constant for those three variations at 14.6 Å and 32.2 Å, respectively. In higher addition of SDS, the globular structure of BSA unfolded into flexible cylinder structure with the radius of 14.4 Å and length of 83.5 Å. The denaturation of BSA was clearly showed by the addition of 40 mM SDS. The structure of BSA in this condition fitted to fractal structure with fractal dimension of 1.1, the block radius of 16.7 Å and the correlation length of 42.5 Å. These results indicated that the addition of SDS at low concentrations has not caused the denaturation of BSA. Meanwhile, the addition of SDS at high concentrations made BSA to unfold that lead to the denaturation of BSA.